One-pot single step to label microtubule with MPA-capped CdTe quantum dots. (May 2018) - Oliveira, Daniel; de Melo, Fernando Menegatti; Toma, Henrique E.
Graphical abstract: Highlights: As an alternative to the biotin-avidin approach, MPA–capped CdTe quantum dots can directly bind microtubules in vitro . MPA–capped CdTe quantum dots provide versatile fluorescent labels in the green spectral region. Surface plasmon resonance techniques allowed to monitor the binding of synthesized QDs to microtubules. Quantum dots-labeled microtubules were successfully visualized with fluorescence microscopy. Abstract: The kinesin-microtubule pair has attracted much attention in recent years due to their promising use in the development of synthetic nanotransport machines. One of the challenges to study such system is how to observe the motility of either kinesin or microtubule. The usual technique for observation of the molecular machinery pair is by fluorescence microscopy, where fluorescent probes are bound to one, or both species, through a biotin-avidin linker. Here, the use of mercaptopropionic acid (MPA)–capped cadmium telluride (CdTe) quantum dots (QDs) as a direct fluorescent labeling agent to microtubule biomolecules is reported. QDs are able to not only bind to microtubules in vitro, but also to fluorescently label them in the red spectral region. Surface plasmon resonance (SPR) studies showed the binding of synthesized QDs to microtubules, while quantum dots-labeled microtubules were successfully visualized with fluorescence microscopy. It is believed QDs adsorbs to the microtubule surface mainly through the coordination of Cd with histidine, cysteine and methionine residues, as well as through interactions of the nanocrystal's carboxylated surface with free amino groups on microtubules.